1991
DOI: 10.1111/j.1095-8649.1991.tb03087.x
|View full text |Cite
|
Sign up to set email alerts
|

The population biology of tench, Tinea tinea (L.), in two gravel pit lakes

Abstract: The populations of tench from two gravel pit lakes of contrasting habitat type were studied. The population density oftench from St Peter's Lake, which has abundant aquatic vegetation was 176 individuals ha-' (102.2 kg ha-') compared to 0.3 individuals ha -' (0.5 kg ha-') in the Main Lake which has very little aquatic vegetation. The results ofageing tench by scales, opercular bones and otoliths were compared; all three structures gave similar results up to 9 years ofage, but thereafter there were difficulties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
2
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 8 publications
3
16
2
1
Order By: Relevance
“…(Gandolfi et al, 1991). However, the maximum age found in Trasimeno Lake was well higher than those reported in literature for other environments (Wright and Giles, 1991;Altindag et al, 2002;Benzer and Yılmaz, 2007;Balık et al, 2009;Gürbüz, 2011;Erguden and Goksu, 2010;Vetlugina, 1992). As regard the wellbeing of fishes, females proved to be in better condition than males, but this result seemed to be affected by the ovary mass; indeed, when the somatic weight was considered in the calculation of condition factor, it was greater in males than females with statistically significant differences.…”
Section: Figurecontrasting
confidence: 44%
See 2 more Smart Citations
“…(Gandolfi et al, 1991). However, the maximum age found in Trasimeno Lake was well higher than those reported in literature for other environments (Wright and Giles, 1991;Altindag et al, 2002;Benzer and Yılmaz, 2007;Balık et al, 2009;Gürbüz, 2011;Erguden and Goksu, 2010;Vetlugina, 1992). As regard the wellbeing of fishes, females proved to be in better condition than males, but this result seemed to be affected by the ovary mass; indeed, when the somatic weight was considered in the calculation of condition factor, it was greater in males than females with statistically significant differences.…”
Section: Figurecontrasting
confidence: 44%
“…07p7 the value calculated for the whole sample was similar to (Altindag et al, 2002), or higher than those reported in the literature (O'maoileidigh and Bracken, 1989;Wright and Giles, 1991;Altindag et al, 1998;Sinis et al, 1999;Miranda et al, 2006;Alaş and Ak, 2007;Balık et al, 2009;Erguden and Goksu, 2009;Erguden and Goksu, 2010;Innal, 2010). The tench in Trasimeno Lake can reach the length of 50.54 cm and the rate of growth was high (0.27 yr −1 ); also the growth performance index testifies the quality of the growth, being its value the higher reported in literature for other populations (Wright and Giles, 1991;Balık et al, 2009;Froese and Pauly, 2011).…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The growth properties of tench (Tinca tinca L., 1758) was investigated in Kesikköprü Dam Lake (3), Vegoritis Lake (23), Lake Dgal Wielki (19), Bayındır Dam Lake (4), Çivril Lake (6), Beyşehir Lake (1, 7), Hirfanlı Dam Lake (8), two gravel pit lakes (25), Seyhan Dam Lake (11), Kapulukaya Dam Lake (18,9), Çamkoru Pond (13) and Trasimeno Lake (20).…”
Section: Introductionmentioning
confidence: 99%
“…It has been introduced into various inland waters in Turkey (Çelikkale, 1988, Geldiay andBalık, 1998). Tench is economically an important fish this species is appreciated from a sport-fishing viewpoint and has been cultivated in Great Britain and Central Europe (Wright and Giles, 1991).…”
Section: Introductionmentioning
confidence: 99%